Biomass and organic waste conversion for sustainable bioenergy: A comprehensive bibliometric analysis of current research trends and future directions - Alao, Kehinde Temitope; Gilani, Syed Ihtsham-ul-Haq; Sopian, Kamaruzzaman; Alao, Taiwo Onaopemipo; Oyebamiji, Damilare Samuel; Oladosu, Temidayo L (Center of Biomass & Renewable Energy (CBIORE), 2024)
The rising demand for renewable energy sources has fueled interest in converting biomass and organic waste into sustainable bioenergy. This study employs a bibliometric analysis (2013-2023) of publications to assess trends, advancements, and future prospects in this field. The analysis explores seven key research indicators, including publication trends, leading contributors, keyword analysis, and highly cited papers. We begin with a comprehensive overview of biomass as a renewable energy source and various waste-to-energy technologies. Employing Scopus and Web of Science databases alongside Biblioshiny and VOSviewer for analysis, the study investigates publication patterns, citation networks, and keyword usage. This systematic approach unveils significant trends in research focus and identifies prominent research actors (countries and institutions). Our findings reveal a significant increase in yearly publications, reflecting the growing global focus on biomass and organic waste conversion. Leading contributors include China, the United States, India, and Germany. Analysis of keywords identifies commonly used terms like